Impact of the Austrian Law on the Development of the Serbian Civil Procedure - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
The work analyses the development and the structure of the Serbian civil procedure law in light of the impact of the Austrian law during 19th and in the first and second half of the 20th century up to the present day. The research results demonstrate the important impact of the Austrian Civil Procedure Law of 1895, which has been assessed in the scholar literature as one of the most modern procedural laws. In this light, all common features of the Serbian procedure laws of 1853,1860, 1865 have been observed, which also started to focus on the court-led dispute, which has been achieved in particular in the law of the Kingdom of Yugoslavia of 1929. The analysis also encompasses the development and the structure, the fundamental concepts of the procedural legislation in the second Yugoslavia, and then in the Republic of Serbia. The structure, the essential converging concepts demonstrate that the common ground of this development was the Austrian Civil Procedure Law of 1895. This applies first of all to the first Federal Law on Civil Procedure of 1956, the Law on Civil Procedure of 1976, the Law on Civil Procedure of the Republic of Serbia of 2004 as well as the applicable law of 2011.